Visualization study on pool boiling critical heat flux under rolling motion. (June 2020) - Tanjung, Elvira F.; Jo, Daeseong
Highlights: Vapor behavior and CHF in response to rolling motion were experimentally investigated. The faster the platform rolled, the earlier the occurrence of CHF. Combination of centrifugal and tangential acceleration affected CHF and vapor behavior. CHF occurred when the heated surface was covered with a large vapor layer for a longer time. Abstract: Vapor behavior and critical heat flux (CHF) mechanism under rolling motion were experimentally analyzed in the present study using a rolling platform system. It was observed that the combination of centrifugal and tangential acceleration affected the vapor behavior and occurrence of CHF. When the platform rolled more quickly, CHF occurred earlier, while CHF occurred every time the platform rolled back after reaching its maximum rolling amplitude. Therefore, the observations of vapor behavior focused on the period during which the platform rolled to its maximum rolling amplitude and then rolled back down. When the platform rolled up to its maximum amplitude, the vapor drifted slowly due to the effect of tangential acceleration, which acted in the opposite direction to the platform. On the other hand, as the amount of vapor grew, it readily detached from the heated surface due to the lower centrifugal acceleration, significantly reducing the size and duration of dry patches on the heated surface. When the platform rolled back down, the tangential acceleration pulled the vapor bubbles down because it acted in the same direction as the platform. Consequently, the vapor bubbles pushed against the bubbles, causing them to coalesce and produce larger dry patches on the heated surface. At the same time, the effect of centrifugal acceleration became stronger, which pushed the vapor towards the heated surface, resulting in vapor could not detach easily from the heated surface. This process led to a further increase in the size and duration of dry patches on the surface. When the platform rolled down, more of the heated surface was covered with a vapor layer for a longer time, hindering the fluid from replenishing the surface and triggering CHF.